Characterization of nanostructured ZnO produced by microwave irradiation - Thongtem T. (2014)
Different molar ratios of Zn(NO3)2 to NaOH were dissolved in de-ionized water, mixed to form solutions with different pH values and heated using 180 W microwave power (80 °C) in ambient atmosphere for 20 min. Wurtzite ZnO nanostructure was detected using an X-ray diffractometer (XRD) and a selected area electron diffraction (SAED) technique. The patterns were in accordance with those of the simulation. Scanning and transmission electron microscopes (SEM and TEM) revealed their nanostructures with different morphologies controlled by molar ratios of the starting agents as well as pH values of the solutions. High resolution transmission electron microscopic (HRTEM) technique shows that the crystallographic planes are aligned in lattice array. Seven different Raman wavenumbers at 334, 378, 410, 440, 541, 575 and 660 cm-1 were used to specify that the products were wurtzite structured ZnO. Photoluminescence (PL) spectra show their emission peaks at 385-394 nm due to the recombination process of free excitons. © 2009 Elsevier Ltd and Techna Group S.r.l.